Effects of traditional Chinese exercises or their integration with medical treatments on cognitive impairment: a network meta-analysis based on randomized controlled trials - Qiu, Jiadong; Kim, Sungmin (Frontiers in Aging Neuroscience, 2024)
Objective This study aims to summarize and critically evaluate the effects of traditional Chinese exercises, both in isolation and in combination with medical treatments, on cognitive impairment. Methods A systematic search of academic databases, including PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang, and VIP, was conducted to identify the randomized controlled trials (RCTs) that evaluated traditional Chinese exercises and their integration with medical treatments for addressing cognitive impairment. Study quality was assessed using the Cochrane Handbook’s Risk of Bias tool. A total of 24 RCTs involving 1,808 participants were included. The primary outcome measures were the Montreal Cognitive Assessment (MOCA) and the Mini-Mental State Examination (MMSE). Subgroup analyses were performed to compare the intervention effects. Results The network meta-analysis revealed that acupuncture combined with Tai Chi (Aandtaiji) showed the most significant improvement in MOCA scores, followed by Qigong. Tai Chi soft ball exercise (Taijiball) demonstrated the greatest improvement in MMSE scores. Conclusion The combination of traditional Chinese exercises with medical treatment is more effective in improving MOCA scores, while traditional exercises alone yield better results to enhance MMSE scores. The extended practice of Tai Chi and Qigong enhances cognitive function in patients with cognitive impairment.